The Implementation of Digital Score Sheet to Increase the Efficiency of Match Evaluations by Tennis Referees - Ricko Irawan; Soedjatmiko Soedjatmiko; Agung Wahyudi (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2026)
The rapid development of information technology in sports has encouraged the digitalization of competition management systems, including the process of score recording by referees. In tennis competitions, score recording is still commonly conducted manually using paper-based score sheets, which are often inefficient, prone to data loss, and difficult to monitor in real time by stakeholders. This study aimed to implement and evaluate the use of an Android-based digital score sheet application, Dik_Tennis Score, to support tennis referees in Central Java in preparation for the Pre-Regional Sports Week (Pra-PORPROV) and the XVII PORPROV events in 2025/2026. The research employed a training-based implementation approach involving tutorials, demonstrations, hands-on practice, and monitoring and evaluation of referees’ ability to operate the application. Participants included regional, national, and white-badge tennis referees who were actively involved in officiating tennis competitions in Central Java. The findings revealed that most referees had previously relied on manual score recording and had limited experience with digital systems. After participating in the training and practical sessions, approximately 80% of the referees were able to independently operate the Dik_Tennis Score application to record match events and transmit results online. The implementation of this digital system improves the efficiency of match administration, facilitates real-time monitoring of match scores, and enables systematic storage of competition data through a web-based database. Therefore, the adoption of an Android-based digital score sheet application has significant potential to enhance the quality of tennis match officiating and support the broader digital transformation of sports competition management.